Kondisi ekosistim mangrove di sub district Liquisa Timor-Leste - Antonio de Jesus (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. The objective of the present study was to determine the condition of the mangrove ecosystem and how to the influence of physic-chemical environment parameters on community structure of mangrove vegetation in Kaitehu Tibar and Ulmera in Bazartete coastal areas District of Liquisa, Timor-Leste. The parameters observed include the condition of mangrove vegetation, soil substrates, plankton abundance and Nutrient Elements in the area. The results showed that, the Sonneratia alba species is the most dominating in Bazartete area, compared with Rhizophora and Brugueira cylindric species, ie 967 threes /ha, 967 threes /ha, and 1333 threes /ha, The results of laboratory analysis quality of physical-chemical conditions of the environment shows that, there are significant differences in soil nutrient substrate in the 3 observation areas. such as follows: Substrate ground, the average content of C-organic were 0.67%, 2.47% and 0.21%, K = 1.17 Me/100g, 1.20 Me/100g , and 1.14 Me/100g; Ca = 32.39 Me/100g, Me/100g 25.83, and 27.09 Me/100g; Me/100g Mg = 11.46, 9.81 and 9.78 Me Me/100g / 100g; Me/100 g Na = 8.47, 8.26 and 9.78 Me/100g Me/100g. The cation concentration at each observation areas is : K = 0.023 mg / l, 0.023 mg / l and 0.046. Ca = 0.05 mg / l, 0.04 mg / l and 0.04 mg / l. Mg= 0.02 mg / l, 0.03 mg / l, 0.026 mg / l, and Na = 0.03 mg / l, 0.03 mg/l and 0.02 mg/l.Keywords. Mangrove ecosystems, mangrove environment habitats, organic matter, Calsium and Magnesium